ANALYSIS PROVISION OF DIRECT INCOME COMPENSATION AND INDIRECT INCOME COMPENSATION ON THE PERFORMANCE EMPLOYEES COMPANY INSURANCE - Said Khaerul Wasif (International Journal of Social Science, 2021)
This study aims to analyze the effect of direct financial compensation and indirect financial compensation on the performance of insurance company employeeS.The sample used is 73 employees. The research technique amalysis use is t is multiple linear regression analysi. The results of this study indicate that partially direct income compensation has an effect on employee performance with a value of sig. 0.000 while the indirect income compensation has the same direct effect on employee performance with sig. 0.015. Meanwhile, direct income compensation and indirect income compensation on the performance of insurance company employees have an effect of 74%. The limitations of this study only discuss 3 variables, namely direct income compensation and indirect income compensation and employee performance. It is hoped that this research can be useful for insurance companies and become a reference for further research regarding the analysis of the provision of direct income compensation and indirect income compensation on the performance of employees company insurance. Keywords: Direct income compensation, indirect income compensation, performance employee performance, insurance